Dual bronchodilation for the treatment of chronic obstructive pulmonary disease: a review of the latest clinical data. (June 2014) - Banerji, Donald; Fogel, Robert; Beeh, Kai-Michael
Treating chronic obstructive pulmonary disease with long-acting bronchodilators improves lung function and patient-reported outcomes such as dyspnea, health-related quality of life and exacerbations. Combinations of long-acting β2 -agonists (LABAs) and long-acting muscarinic antagonists (LAMAs) are an alternative treatment recommendation for patients in GOLD Groups B to D and those who remain symptomatic when treated with a single bronchodilator. This review summarizes evidence supporting the efficacy and safety of fixed-dose LABA/LAMAs glycopyrronium/indacaterol (QVA149) and umeclidinium/vilanterol. Considerable clinical trial data are available demonstrating improvements in lung function and patient-reported outcomes with QVA149 and umeclidinium/vilanterol compared with their monocomponents and other comparators. As data supporting the efficacy and safety of LABA/LAMA fixed-dose combinations continue to emerge, dual bronchodilation may feature increasingly in future chronic obstructive pulmonary disease treatment algorithms.